ISSUES OF ANTROPOCENTRIC STUDY OF MODERN LINGUISTICS - Nozima , Ohunova Alisher qizi (Educational Research in Universal Sciences, 2023)
The article represents the anthropocentric paradigm that mainly focuses on cognitive linguistics and linguaculturology. There is also analyzed the concept as a main part of cognitive research and linguacultural concept as well. There is presented some famous scholars who have done valuable research in the anthropocentrism. Some conclusions have been made according to the article.